Prospects for people who use drugs: Maintenance, recovery or progress? An analysis of motivation to change in individuals attending for opioid agonist prescribing (OAP) in a general practice setting. (3rd September 2018) - Robertson, Roy; Copeland, Lorraine; Beresford, Hannah; Elton, Rob; Carson, David
Abstract: Aims : To evaluate the characteristics and potential for change in a group of opiate dependent patients. Methods : A convenience sample of individuals receiving a prescription for an opiate substitute were recruited during a consultation with their general practitioner in an NHS practice located in a city in Central Scotland with a high incidence and prevalence of opiate drug use. Participants completed a standardised questionnaire (Christo Inventory for Substance Misuse) and self-allocated to a motivational group representing willingness to consider change of prescription. Findings : The group had a high level of comorbidity and a low interest in change of prescription. Stability of drug use was found to be common even in the presence of frequent mental and physical health problems. Unemployment was high in a largely male population who had a high need but low uptake for psychological help. Conclusions : For study participants, potential for change seems limited with medium to long-term continuation of an opiate agonist treatment plan appropriate. They represent a high risk group for death from various causes and may be protected by their current situation. Engagement with other health and social care professions is poor. Implications for clinical practice are that OAP is, for many, a longer term prospect and that recovery, or progress, should be assessed by a wider range of measures than just drug intake.